Problema análogo ao de cafiero para equações diferenciais com retardamento - Sverzut, Rosa Lucia (1978)
The main purpose of this paper is to solve a problem in Differential Equations with time Delay: Given f:[ 0, ∞) xCH → Rn, suppose that the problem with inicial condition (1) {x = f (t, xt ) {xt0 = ψ has a unique solution for to t0 ≥ 0 fixed and ψ running over a dense subset A of CH. Then, what about the uniqueness outside A?" This problem is analogous to one inicially proposed by Cafiero for Ordinary Differential Equation Problem (1) is solved taking in account that its uniqueness is a generic property on CH if f is a continuous application that takes bounded sets in bounded sets.